Concurrent medical conditions among pregnant women - ignore at their peril: report from an antenatal anesthesia clinic - Carolyn F. Weiniger; Sharon Einav; Uriel Elchalal; Vladislav Ozerski; Daniel Shatalin; Alexander Ioscovich; Yehuda Ginosar (BMC, 2018)
Abstract Background Care of pregnant women with concurrent medical conditions can be optimized by multidisciplinary antenatal management. In the current study we describe women with concurrent medical conditions who attended our antenatal anesthesia clinic over a 14-year period, 2002-2015 and, based on the findings, we suggest new policies, strategies and practices to improve antenatal care. Methods In 2002, an antenatal anesthesia clinic was established in Hadassah Medical Center. Each consultation focused on the concurrent medical condition. A written anesthesia strategy according to the medical condition and its anesthesia considerations was discussed and given to the patient. Data regarding clinic visits were recorded. Results A total of 451 clinic women attended the antenatal anesthesia clinic. Maternal age was 31.7 ± 6.0 years (mean ± SD), with gestational age of pregnancy 33.0 ± 5.4 weeks at the clinic visit. Musculoskeletal conditions (23% of all the women seen) were the most frequent concurrent conditions, followed by anesthesia related concerns 20%, neurologic conditions 19%, and cardiac conditions 15%. Women were provided plans that were deliberated carefully rather than being concocted during labor. Conclusions A wide range of concurrent medical conditions was seen in the antenatal anesthesia clinic, however fewer women attended the clinic than expected according to known population frequencies of concurrent medical conditions. Women with concurrent medical conditions should have labor and anesthesia plans considered during the nine months of pregnancy, prior to delivery, and hospitals should have a means of obtaining this information in a timely manner. Finally, there is a need to develop additional antenatal anesthesia clinics.